Awareness of Gout and Hyperuricemia in a Sample of the Adult Population in Iraq - Shaimaa Jubair; Sami Shihab; Naqaa Mousa (Al-Anbar Medical Journal)
Background: Gout is the most common type of inflammatory arthritis in men and postmenopausal women.The incidence and prevalence of hyperuricemia and gout were increased all over the world even among developed countries. Materials and methods: A cross-sectional study was conducted at the Rheumatology Unit of Baghdad Teaching Hospital in Medical City, Baghdad, Iraq from October 2020 to April 2021. A total of 247 subjects were included in the study. Data were collected using a pre-constructed data collection sheet by face-to-face individual interviews. The sheet includes demographic characteristics, gout-related questions regarding the etiology, suspected predisposing agents, complications, diagnostic methods, food-related, clinical manifestations among studied cases, and attitudes of the gout patients among the study sample. Results: Of 247 subjects, there were 67.2% (n = 166) males, 27.9 (n = 69) from the age group 40-49 years, 36.4% (n = 90) from Baghdad city, 25.5% (n = 63) university graduates, 19.9% with good income, 70.5 (174) employed, 221 (89.5%) married, 85% (n = 210) non-smokers, and 8.9% (n = 22) with family history of gout. Overall, 59 (23.9%) of the participants had a high level of awareness whereas low awareness levels accounted for 41.3% (n = 102). The awareness level showed a statistically significant association with education level, occupation, economic status, smoking habit, family history of gout, and patients with gout (P-value < 0.05). Conclusion: There was a high proportion (41.3%) of the participants with a low level of awareness about gout and hyperuricemia. The awareness level among the participants was related to the education level, occupation, economic status, smoking habit, family history of gout, and patients with gout.